The effectivness of apprenticeship training : a within track comparison of workplace-based and school-based vocational training in Hungary - Horn, Dániel [Verfasser] (Corvinus University of Budapest / Department of Human Resources, 2014)
"Although apprenticeship training has been praised for its effectiveness in smoothing the school-to-work transition of non-college bound students, most studies rely on cross country or cross track comparisons. This study compares apprenticeship training students with non-apprentices within educational track using a rich database and a unique set of observable individual level characteristics as well as local labor market fixed effects to control for the potential selection bias. The results show that there are no significant differences in employment chances between apprentices and non-apprentices within just a year after graduation. Although, in small subsamples of the population, significant differences can be found, these are most likely due unobserved heterogeneity. However, even if these observed differences are unbiased, they are more likely due to the superior screening of the larger firms rather than their superior training." (Authors' abstract)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.2 Osteuropa; Berufsausbildung; Effektivität; Betriebliche Berufsausbildung; Schulische Berufsausbildung; Vergleich; Ungarn